2008
DOI: 10.2220/biomedres.29.233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a neuraminidase inhibitor (oseltamivir) on mouse jump-down behavior via stimulation of dopamine receptors

Abstract: Oseltamivir (Tamiflu ® , Roche Laboratories, Inc.) is a neuraminidase inhibitor that can cause jumpdown behaviors in children. There is a mouse slip-down model, in which the dopamine D2 receptor activity is increased by serum sialoglycolipids and the mouse jump-down behavior appears in response to the dopamine D2 receptor agonist, PPHT. The present study examined the effect of oseltamivir on jump-down behavior in mice. Oseltamivir sialylates a serum glycolipid and this modified glycolipid induces jump-down beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
1
14
0
1
Order By: Relevance
“…This mechanism has been implicated in an animal study linking oseltamivir with abnormal behavior. 12 Oseltamivir may assert a similar influence on the human nervous systems and cause prominent psychiatric symptoms. Further investigations by human experimental studies are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism has been implicated in an animal study linking oseltamivir with abnormal behavior. 12 Oseltamivir may assert a similar influence on the human nervous systems and cause prominent psychiatric symptoms. Further investigations by human experimental studies are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Suzuki et al [64] reported that oseltamivir sialylates a serum glycolipid and that this modified glycolipid induced jump-down behaviour via stimulation of dopamine D2 receptors; they suggest that this mechanism may be involved in the abnormal behaviour seen in some children taking oseltamivir.…”
Section: Toxicity and Toxicokinetics Studies In Juvenile Rats: An mentioning
confidence: 99%
“…The modules are followed by some humoral glycolipids. A sulfated Galbeta1-4GlcNAclipid (3-O-Sulfo-Beta-D-Galactosyl-(1->4)-N-Acetyl-Beta-D-Glucosamine-lipid: sG1-4GN) promotes the serotonergic module regulating the emotional behaviors for not-wasting the physical strength [3,4], GalNAcalpha1-3GalNAc-lipid (GalNAcalpha1->3GalNAc-lipid: GN1-3GN) promotes the adrenergic module inducing the stress-coping behaviors [5,6], sulfated Fucalpha1-2Glc-lipid (Fucalpha1-2[6OSO3]Galbeta1-4Glcbeta-lipid: sF1-2G) protects the cholinergic module keeping the valid stresscoping memories from the ischemia-stress, as an adaptogen does [4,7,8], and Sialalpha2-3Gal-lipid (NeuAcalpha2-3Gal-lipid: S2-3G) promotes the dopaminergic module integrating the emotion and recognition-behaviors [9,10,11]. Now, major depression patients have the functional abnormalities in their amygdala, caudate nucleus and hippocampus [12], manic patients have the functional abnormalities in their amygdala, ventral striatum and hippocampus [13], and schizophrenia patients have the functional abnormalities in their frontal and temporal lobes [14].…”
Section: Introductionmentioning
confidence: 99%